2020
DOI: 10.4314/ahs.v20i4.37
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral oedipism: a case of extreme self-harm in an African society averse to self-mutilation

Abstract: Nil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Our review of the literature included 54 articles and 75 patients who self-enucleated at least one eye. 1,3–55 The features of these patients are described in Table 1. The patients had an average age of 37 years (±14 SD) and were 50.7% male.…”
Section: Resultsmentioning
confidence: 99%
“…Our review of the literature included 54 articles and 75 patients who self-enucleated at least one eye. 1,3–55 The features of these patients are described in Table 1. The patients had an average age of 37 years (±14 SD) and were 50.7% male.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, published works on the subject continue to be case reports on one or two cases with uniocular involvement predominating. [ 1 2 4 5 13 16 17 ] An extensive literature search, via MEDLINE, reported that there were 37 published papers on the subject. [ 1 ] These papers documented 56 patients (71 globes) worldwide who had auto-enucleation in at least one eye.…”
Section: Discussionmentioning
confidence: 99%
“…So far the only report of self-enucleation from Nigeria was that by Nnadozie et al . [ 17 ] who documented bilateral oedipism in a 24-year-old farmer. Their patient was a known cannabis user who also had drug-induced psychosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, most cases described in the literature of oedipism were due to severe mental disorders, especially psychosis [ 4 ]. Though oedipism was initially thought to be related to preoccupations with sins and higher deities, several recently published case reports highlight that this is a universal phenomenon that can be observed in people with different religious and cultural backgrounds [ 4 , 15 ]. our patient was under the influence of alcohol when he attempted to self-amputate his left arm; it was difficult to ascertain whether he was also experiencing delusions or hallucinations that guided this episode of self-mutilation.…”
Section: Discussionmentioning
confidence: 99%